A comparative in vitro digestion trial using inoculum of livestock from south Turkana and Kitale, Kenya - Coppock, D. Layne; Ellis, J.E.; Waweru, S.K. (Cambridge University Press, 1988)
Evaluates the dry-matter digestibilities of some important herbaceous and browse forages from an arid rangeland in north-western Kenya in a comparative in vitro trial using rumen fluid from indigenous sheep, goats, camel, and Merino sheep.